1996
DOI: 10.1159/000109910
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease in Populations of African Origin A Review

Abstract: Several studies have reported a lower prevalence of Parkinson''s disease (PD) in populations of African origin than in populations of European origin, raising the possibility that the former are protected against PD. However, the confounding effects of low case ascertainment and high selective mortality on PD prevalence estimates in populations of African origin cannot be ruled out at this time. One hypothesis consistent with available data is that populations of African origin are vulnerable to vascular parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This strong association persisted in the multivariate analysis and was not confounded by inclusion of other risk factors into the final model. Populations of African origin have been shown to have a greater prevalence of cardiovascular disease than white populations, in particular the risk factor hypertension [37,38]. Interestingly, studies in these populations report among the lowest prevalence ratios of PD, which supports the belief that there is a protective effect of hypertension for disease development.…”
Section: Discussionmentioning
confidence: 94%
“…This strong association persisted in the multivariate analysis and was not confounded by inclusion of other risk factors into the final model. Populations of African origin have been shown to have a greater prevalence of cardiovascular disease than white populations, in particular the risk factor hypertension [37,38]. Interestingly, studies in these populations report among the lowest prevalence ratios of PD, which supports the belief that there is a protective effect of hypertension for disease development.…”
Section: Discussionmentioning
confidence: 94%
“…Studies to assess the prevalence of PD in African American populations show varied results. 11,12 A review of 20 studies 13 concluded that differences in prevalence in African Americans com-pared with European populations remain unproven. Some evidence suggests that PD is underdiagnosed in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…PD in people of African-Caribbean origin living in the UK has been implicated to present with atypical features, such as lateonset disease, L-dopa hyporesponsiveness, and early cognitive dysfunction [3,25]. An imaging study has shown that the atypical Parkinsonian phenotype seen in AfricanCaribbean and Indian patients in several London hospitals represents an L-dopa-refractory form of PD separate from multiple system atrophy (MSA) or progressive supranuclear palsy (PSP), given that no neuroimaging signs of these entities were observed and that cerebral vascular lesion load was also not significantly increased in these patients [11].…”
Section: Discussionmentioning
confidence: 99%